2023
DOI: 10.3389/fpls.2023.1265700
|View full text |Cite
|
Sign up to set email alerts
|

Drought and heat stress on cotton genotypes suggested agro-physiological and biochemical features for climate resilience

Muhammad Mubashar Zafar,
Waqas Shafqat Chattha,
Azeem Iqbal Khan
et al.

Abstract: This study aimed to investigate the impact of individual drought, heat, and combined drought and heat stress on twelve cotton genotypes, including eight tolerant and four susceptible genotypes. A field experiment was carried out by employing a randomized complete block split-plot design, with treatments (control, drought, heat, drought + heat), and cotton genotypes assigned to the main plots and sub-plots respectively. The results showed that the combined stress had a more severe impact on the yield and fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Lastly, three cotton strains BH-184, BWS-8, and BWS-12 contributed 11.896%, 47.193%, and 16.063% to the variations (Table 8). Several researchers used principal component and biplot analysis in categorising cotton genotypes under different circumstances and found it very useful in classifying the genotypes based on their performance (Zafar et al, 2023Zafar et al, 2022and Zafar et al, 2021 The PC1/PC2-based biplot analysis also confirms the results obtained through cluster analysis, correlation analysis and principal component analysis. The biplot showed that seed cotton yield has a significantly positive association with key yield-contributing traits, including net photosynthetic rate, superoxide dismutase, total chlorophyll contents, bolls per plant, sympodia per plant, nodes per plant and plant height as their corresponding lines lay near to the corresponding line of seed cotton yield while the highest negative association with hydrogen peroxide as its corresponding line was in completely opposite direction (Figure 3).…”
Section: Bwsmentioning
confidence: 73%
“…Lastly, three cotton strains BH-184, BWS-8, and BWS-12 contributed 11.896%, 47.193%, and 16.063% to the variations (Table 8). Several researchers used principal component and biplot analysis in categorising cotton genotypes under different circumstances and found it very useful in classifying the genotypes based on their performance (Zafar et al, 2023Zafar et al, 2022and Zafar et al, 2021 The PC1/PC2-based biplot analysis also confirms the results obtained through cluster analysis, correlation analysis and principal component analysis. The biplot showed that seed cotton yield has a significantly positive association with key yield-contributing traits, including net photosynthetic rate, superoxide dismutase, total chlorophyll contents, bolls per plant, sympodia per plant, nodes per plant and plant height as their corresponding lines lay near to the corresponding line of seed cotton yield while the highest negative association with hydrogen peroxide as its corresponding line was in completely opposite direction (Figure 3).…”
Section: Bwsmentioning
confidence: 73%
“…Herewith, in several works, the AOS status under heat stress at the generative stages of plant development was focused on. Thus, activity of SOD, CAT and POX, as well as content of proline was found higher in the heat resistant cultivars on the stage of flowering in the field conditions by means of a tunnel constructed using bamboo sticks and plastic sheets (Zafar et al, 2023). In contrast, the resistant cultivars under the effect of excessive temperatures were found to retain values of oxidative stress markers, including hydrogen peroxide and MDA, close to the control ones.…”
Section: Introductionmentioning
confidence: 78%
“…As it was pointed out, in the field experiments on the stage of cotton flowering activities of catalase, SOD, POX as well as contents of proline under heat stress were found increased in the resistant cultivars, while contents of MDA and hydrogen peroxide were typically lower in them (Zafar et al, 2023). Yousaf et al (2022) demonstrated significant positive correlation of seed cotton yield with activity of POX (r = 0.974) and SOD (r = 0.868) under heat stress field conditions by shift in sowing period.…”
Section: Correlations Between Growth Response Of Plants To Heat Stres...mentioning
confidence: 85%
“…Climate models predict the global surface temperature will increase by 3–5 °C in the next century. This could lead to more frequent occurrences of droughts and floods [ 38 ]. Thus, this study aimed to assess the affordability of increasing the physiological and molecular resistance of different cultivars of wheat to drought and water scarcity upon biopriming with endophytic fungi.…”
Section: Discussionmentioning
confidence: 99%